An Innovative Education Model to realize Ideal Education System (International Journal of Scientific Research and Management (IJSRM), 2015)
Education is the most important thing for any country to develop and prosper. Education moulds the character and intelligence of individuals. It also provides the talent and motivation to every person. The conventional education system at higher education level is analog to brick and mortar type business system, where a student get systematic education from college/University by physically attending required courses regularly (Full time/part Time). In this paper we have presented an Ideal Education System model by considering its various characteristics under Input conditions, Systems requirements, Output conditions and Environmental & social conditions. These characteristics are analyzed with an objective to achieve the goal. We have studied the possibility of realizing our Ideal Education System through Online Education using E-education model. Finally a comparison is made between Conventional Education Models and Online Eeducation model called Mobile Education Model